Where would you turn for help? Older adults' knowledge and awareness of community support services - Margaret Denton; Jenny Ploeg; Joseph Tindale; Brian Hutchison; Kevin Brazil; Noori Akhtar-Danesh; Monica Quinlan (McMaster University, Research Institute for Quantitative Studies in Economics and Population (QSEP), 2009)
Community support services (CSSs) enable persons coping with health or social problems to maintain the highest possible level of social functioning and quality of life. Access to these services is challenging because of the multiplicity of small agencies providing these services and the lack of a central access point. A review of the literature revealed that most service awareness studies are marred by acquiescence bias. To address this issue, service providers developed a series of 12 vignettes to describe common situations faced by older adults for which CSSs might be appropriate. In a telephone interview, 1152 older adults were presented with a series of vignettes and asked what they would do in that situation. They were also asked about their most important sources of information about CSSs. Findings show awareness of CSSs varied by the situation described and ranged from a low of 1% to 41%. The most important sources of information about CSSs included informational and referral sources, the telephone book, doctor's offices, and through word of mouth.
Keywords: I18; 330; Community Support Services; awareness; knowledge; acquiencence bias; vignette methodology; Kommunale Dienstleistung; Kanada